Pengaruh Return on Assets (ROA) , Debt to Equity Ratio (DER) , dan Current Ratio (CR) terhadap Nilai Perusahaan pada Jakarta Islamic Index 70 - Lisa Aprilia Febrian; Andang Sunarto; Khairiah Elwardah (UNIVED Press, 2022)
This study aims to determine the effect of Return On Assets, Debt To Equity Ratio and Current Ratio partially and simultaneously on firm value on the Jakarta Islamic Index 70 (JII70) in 2018-2020. Several previous studies on firm value showed different results. So, other research needs to be done to retest the theory of firm value. This research is a type of correlational analysis research with a quantitative approach. The research population was 70 companies on the Jakarta Islamic Index 70. The sampling method used the purposive sampling technique. So that the sample in this study was 28 companies during 2018-2020. The source of data collection used is in the form of numbers obtained from the www.idx.co.id website and the official website. The data analysis technique used multiple linear regression analysis. The data analysis process carried out is descriptive statistics, basic assumption test, classical assumption test, hypothesis test and determination coefficient test. The results showed that partially Return On Assets had no significant effect on firm value. Debt To Equity Ratio has a significant negative effect on firm value. While the Current Ratio has a significant effect on firm value. Simultaneously, the Debt To Equity Ratio and the Current Ratio have a simultaneous effect on the firm value of 7.1%. While the remaining 92.9% was influenced by other factors that were not included in this study.